HUBUNGAN ANTARA PERILAKU MENONTON SINETRON PERCINTAAN DENGAN PERILAKU PACARAN PADA SISWA- SISWI YAYASAN ISLAMIYAH DI SMA ETHIKA PALEMBANG - Vusvi Eka Sari Zendrato; Muhajirin Muhajirin; Kiki Cahaya Setiawan (Psikis : Jurnal Psikologi Islami, 2016)
Courtship behavior is a series of joint activities tinged intimacy (such as a sense of ownership and self-disclosure) as well as their emotional attraction between men and unmarried women with the aim to know each other and see the fit between one another consideration before marriage, but also many dents student doing courtship behavior on the grounds of the main factors to watch soap operas frequent lovemaking makes bad influence on students. Behaviour love to watch soap operas is how seringkan activities using the eye or looking at television or watch a soap opera soap opera featuring romance.         This  study  aims  to  test  empirically  whether  there  is  a  relationship  between  the  behavior  of watching  soap  opera  romance  with  dating  behavior.  Behaviors  to  watch  soap  operas  romance dalah independent variable, while the dependent variable is a courtship behavior. The hypothesis is "no relationship between the behavior to watch soap operas with courtship behavior in students at SMA Foundation Islamiyah Ethika Palembang.        The  population  in  this  study  are  272  students  at  the  high  school  Yayasan  Islamiyah  Ethika Palembang, and the sample was 155 students at SMA Foundation Islamiyah Ethika Palembang. By using  the  quantitative  research  methods,  sampling  technique  that  by  random  sampling  technique with reference to the table Isac and mihcel on the error level of 5%. Methods of data analysis used to test the hypothesis of the research is simple regression analysis.         All  calculations  were  performed  using  the  data  analysis  computer  program  SPSS  (statistical packager for social science) version 20. The results of the analysis obtained correlation coefficient of r = 0.765 and p = 0.000 significance, means p <0.01, so the hypothesis is proven or accepted, can concluded that there is a very significant positive relationship between behavior to watch soap operas  romance  with  courtship  behavior  in  students  at  SMA  Foundation  Islamiyah  Ethika Palembang.